Persistent endocrine-disrupting chemicals found in human follicular fluid stimulate the proliferation of granulosa tumor spheroids via GPR30 and IGF1R but not via the classic estrogen receptors. (February 2019) - Gogola, Justyna; Hoffmann, Marta; Ptak, Anna
Abstract: Epidemiological studies have found that women have detectable levels of organic pollutants such as hexachlorobenzene (HCB), 2, 2-dichlorodiphenyldichloroethylene (p, p'-DDE), polychlorinated biphenyl 153 (PCB153), perfluorooctanoate (PFOA), and perfluorooctane sulfonate (PFOS) in their follicular fluid. Thus, these compounds may directly affect the function of granulosa cells within the ovary and may promote granulosa cell tumor (GCT) progression. Two human GCT cell lines, COV434 and KGN, have been used as in vitro model systems to represent juvenile (JGCT) and adult (AGCT) GCT subtypes, respectively. In this study, we found that basal expression of estrogen receptor 1 ( ESR1 ), estrogen receptor 2 ( ESR2 ), and insulin-like growth factor 1 receptor ( IGF1R ) was higher in the AGCT subtype than in the JGCT subtype. All of the compounds acted as mitogenic factors at low nanomolar concentrations in the JGCT and AGCT forms of GCT. Interestingly, PFOA, PFOS, and HCB stimulated cell proliferation through IGF1R, whereas p, p'-DDE acted through GPR30. Moreover, a mixture of the five compounds also significantly stimulated granulosa cell proliferation; however, the observed effect was lower than predicted. Interestingly, the proliferative effect of a mixture of these compounds was dependent on IGF1R and GPR30 but independent of the classic estrogen receptors. Taken together, our results demonstrate for the first time that mixtures of persistent organic pollutants present in follicular fluids may induce granulosa tumor progression through IGF1R and GPR30 by acting as mitogenic factors in granulosa cells. Highlights: HCB, p, p'-DDE, PCB153, PFOA, and PFOS stimulate COV434 and KGN cell proliferation. A mixture of these compounds is less potent than predicted based on the activities of the individual compounds. The classic estrogen receptor pathway is not involved in the proliferative effects of the EDC mixture. The EDC mixture stimulates cell proliferation through the GPR30 and IGF1R pathways.